Fysisk aktivitet, inaktivitet och kapacitet hos gymnasieungdomar - Mikaelsson, Katarina (Luleå tekniska universitet, Hälsa och rehabilitering, 2012)
A change in behaviour with reduced physical activity and an increased sedentary behaviour among children and adolescents may be a threat to their future health. The literature shows that physical activity decreases through adolescence and the habits from childhood and adolescence have a tendency to become manifest. It is therefore particularly important to investigate the physical activity of adolescents and its effect on physical capacity, in conjunction with underlying factors that might have an impact on how active adolescents are. The overall aim of this thesis was to describe physical activity and its relation to physical capacity of adolescents from upper secondary schools and to highlight the reasoning about physical activity and health among physically inactive adolescents’.Paper I was a survey in which 884 adolescents from Northern Sweden participated. The adolescents were asked questions about their physical activity together with questions with a relation to physical activity. To put the physical activity in relation to physical capacity the adolescents were at the same time asked if they could participate in future studies concerning physical capacity (Paper II and III) and participation in an interview study (Paper IV). In paper IIIII physical capacity was assessed by aerobic capacity, muscle strength and balance (n = 99). In Paper II physical capacity was compared between physically active and physically inactive men and women. In paper III, the relation between physical capacity and self-rated physical activity and time spent sitting were investigated. In paper IV adolescents who did not meet the WHO recommendation of physical activity were interviewed and asked to describe their experience about physical activity and health.The results from paper I - III show that there was a group of adolescents who did not meet the recommendations for physical activity and that it affected their physical capacity. There was a clear gender difference; the men were physically active at higher intensity levels ...